Essays on Financial Globalisation - Emter, Lorenz (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2022)
This dissertation is a collection of three essays on financial globalisation. A common theme running through the essays in this dissertation is the importance of global factors shaping national macro-financial outcomes with a focus on policy options for domestic policy makers which can tame the ramifications of financial globalisation. The first essay studies the international transmission of shocks to global financial conditions on macroeconomic tail risks in advanced and emerging economies. The chapter shows that contractionary financial and monetary policy shocks originating in the U.S. cause elevated downside risks to output growth around the world. By tightening financial conditions globally, these shocks affect the left tail of the conditional output growth distribution disproportionately. This effect is particularly pronounced for countries with less flexible exchange rate arrangements, higher foreign currency exposures, and higher levels of private sector leverage. This suggests that policymakers face a trilemma, in which the exchange rate regime and macro-prudential policies matter for downside risks to growth. The second essay extends the literature on extreme episodes in international capital flows by providing empirical evidence that domestic variables are significantly related to the probability of incurring sharp reversals in capital inflows controlling for global push factors. In particular, negative growth shocks combined with high levels of leverage in the domestic private sector are a significant determinant of sudden stops. This is in line with real business cycle models including an occasionally binding credit constraint and income trend shocks. By limiting excessive credit growth, countercyclical macroprudential policy could, hence, also serve to reduce the susceptibility of capital inflows to sudden stops. The third essay examines the impact of automatic exchange of information (AEOI) treaties between tax authorities on cross-border investment positions in tax haven countries. Employing a confidential sectoral breakdown of data on bilateral bank deposits, we find that the AEOI significantly reduced cross-border deposits in tax havens, in particular by households. Moreover, the portfolio and direct investment assets of tax haven entities in non-haven countries fell significantly after AEOI introduction. However, we also document evidence of deposit shifting by the household sector and observe larger foreign direct investment positions and non-bank financial institutions? deposits between tax haven countries, suggesting an increased use of shell companies since AEOI introduction. Hence, the chapter highlights the importance and effectiveness of multilateral policy making in order to curb one particular challenge posed by financial globalisation in the form of tax evasion, while highlighting some of the remaining challenges for policymakers.
APPROVED
Keywords: Global financial cycle; Growth-at-Risk; International spillovers; International capital flows; Tax havens; International tax treaties